Productivity and Profitability of the Sugarcane Production in the State of Sao Paulo, Brazil - Amorim, Fernando Rodrigues de; Ospina Patino, Marco Tulio; Bartmeyer, Petra Maria; Lopes Santos, David Ferreira [UNESP] (Springer, 2020)
The competitiveness of the sugarcane production chain requires investments in new technologies and management practices at all stages of production, especially in tillage or soil preparation and planting activities. Then, which production system presents the best productive and economic performance for the sugar cane crop in Brazil? The objective of this research was planned to answer this question, and due to differences in the production structure of sugarcane mills (SMs) and sugarcane independent producers (SIPs), the analysis was intended to explore data from for these two groups. A significant sample with data from 31 SMs and 42 SIPs in the State of Sao Paulo, Brazil, and quantitative modeling, based on linear programming, were used to determine the best production systems. The results showed that conventional fixed-rate tillage and the use of fixed-rate pre-sowing seedlings lowered the costs for SIPs and SMs, while variable-rate localized tillage; semi-mechanized tillage with fixed rate; tillage fixed-rate seedlings; and the fixed-rate pre-sprout seedlings increased the revenues for the mills. SIPs that use fixed-rate conventional tillage; conventional fixed-rate tillage; fixed-rate mechanized planting; and fixed-rate semi-mechanized planting increased the profitability or sugarcane producers. SIPs that renew 5% of their sugarcane area attained a productivity of 85 t ha(-1) compared to 88 t ha(-1) for SMs.
Keywords: Costs optimization; Profit maximization; Sugarcane; Tillage; Planting